2021
DOI: 10.21462/jeltl.v6i3.609
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study of Academic Vocabulary in a Novice Student’s Writing at a UK University

Abstract: <em>Mastering appropriate writing style is one of the challenges frequently experienced by novice student writers entering higher education. Developing academic writing skills is, however, crucial for students new to academic settings since written assignments constitute the main form of assessment in tertiary education. Novice student writers thus need to acquire the writing conventions used in academic settings to achieve success in high-stakes assessment. Underlying success in academic writing is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The inadequacy of textbooks as the primary resource in the classroom is a significant limitation. As found by Therova (2021), reading resources play a vital role in the acquisition of new academic vocabulary items. Consequently, the resorted to alternative sources to gain lexical input, although many are still determining whether they are gaining any.…”
Section: Lacksmentioning
confidence: 91%
See 1 more Smart Citation
“…The inadequacy of textbooks as the primary resource in the classroom is a significant limitation. As found by Therova (2021), reading resources play a vital role in the acquisition of new academic vocabulary items. Consequently, the resorted to alternative sources to gain lexical input, although many are still determining whether they are gaining any.…”
Section: Lacksmentioning
confidence: 91%
“…Thus, its mastery would necessitate learners' ability to accurately comprehend and produce academic discourses (Nation, 2013), especially for those pursuing university-level programs in English-medium settings (Coxhead, 2021). Over the years, numerous studies have shown the role of academic vocabulary knowledge in improving learners' academic reading comprehension (Lawrence et al, 2022), academic writing (Csomay & Prades, 2018;Therova, 2021), listening comprehension (Dang, 2022;Ha, 2021), speaking assessments, such as presentations or debates (Smith et al, 2020;Yunus et al, 2016) as well as overall academic accomplishments (Skjelde & Coxhead, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Academic writing is one of the formal writing styles used in schools and colleges. Due to its formality, the writer requires carefulness to write complete sentences and organize them specifically (Ariyanti, 2016;Khamkhien, 2021;Therova, 2021). The writer also needs to answer and demonstrate an understanding of the subject discussed in academic writing.…”
Section: Introductionmentioning
confidence: 99%
“…This section presents previous research about L2 learners' metacognitive knowledge in vocabulary learning. These studies, although addressing metacognitive knowledge, used alternative terms, such as beliefs (Moir & Nation, 2002;Chung & Fung, 2022), perspectives (Therova, 2021), or thoughtful use of strategies (Cornell et al, 2016). Research has shown that learners' beliefs have a significant impact on how they approach learning, which, in turn, affects the learning outcomes.…”
Section: What Metacognitive Knowledge Do Vocabulary Learners Have?mentioning
confidence: 99%
“…Relatable sentiments were felt by the learners in Cornell et al (2016), who reported their motivation to select words that their teacher potentially "will ask for" in subsequent tests (p. 837). Both Cornell et al (2016) and Therova (2021) found that EAP teachers were perceived by the participating students as vocabulary providers and source of lexical input. For effective teaching and learning to occur, teacher cognition and practice should be informed by research (Macalister, 2012).…”
Section: Teachers' Influences On Learners' Approaches To Vocabularymentioning
confidence: 99%